In vitro Shoot Regeneration of the Aquatic Ornamental Plant – Rotala rotundifolia (Buch-Ham. Ex Roxb.) Koehne (Journal of Bio-Science, 2026)
Rotala rotundifolia (Buch.-Ham. ex Roxb.) Koehne is a popular aquatic ornamental plant possess with ecological and commercial value. The plant species are critical in position due to habitat loss and overharvesting. Thus, efficient and rapid propagation strategies are highly desirable. This study aimed to establish an efficient in vitro regeneration protocol for conservation and mass propagation. Nodal segment and shoot tip explants were cultured on Murashige and Skoog (MS) medium supplemented with various concentrations and combinations of cytokinins (BAP, kinetin) and auxins (IBA, NAA). Optimal shoot proliferation was achieved from nodal segment explants on full-strength MS medium containing 1.0 µM/L BAP, with a maximum of 47.12 ± 0.86 shoots per culture and 4.97 ± 0.16 cm shoot length. The combination of 2.0 µM/L BAP and 1.0 µM/L IBA were used for further enhancement of shoot induction and elongation. Liquid MS medium was more suitable for shoot regeneration compared to solidified MS medium supplemented with 2.0 µM/L IBA, which exhibited the highest relative plant regeneration frequencies  93.33% of rooting and 15.92 ± 2.59 roots per shoot. Acclimatized plantlets grown in a pot containing garden soil and cocopeat (1:1) substrate showed 90% survival and vigorous growth. This protocol offers a reproducible platform for large-scale propagation and conservation of R. rotundifolia species.J. Bio-Sci. 33(2): 29-42, 2025